Histopathological Study of Upper Gastrointestinal Tract Endoscopic Biopsies - Nazrin, Mosammat Suchana; Ferdous, Nur E Jannatul; Saha, Madhusudan; Rabbi, Fahmi Iqbal (Journal of Current and Advance Medical Research, 2019)
Background: Diseases of gastrointestinal tract are a major cause of morbidity and mortality. Objective: This study was carried out to determine the spectrum of histopathological lesions of upper gastrointestinal tract. Methodology: This retrospective study was conducted in the Department of Pathology at North East Medical College, Sylhet, Bangladesh during a 36 months period from January 2013 to December 2015. Endoscopies were performed using Olympus 150, forward viewing upper GI endoscope. The biopsy specimens received were fixed in 10.0% formalin and routinely processed in Haematoxyline & Eosin stain. Results: The present study included 135 endoscopic biopsies. The mean age with SD of the study population was 53.20±16.09 years. Among 53 cases of esophageal biopsies 8(15.08%) cases showed non-neoplastic lesions and 45(84.92%) cases were neoplastic of which 39(73.6%) cases and 6(11.32%) cases were squamous cell carcinoma and adenocarcinoma respectively. Among 6 cases of gastro esophageal junction biopsies 3(50%) cases showed non-neoplastic lesions and 3(50%) were neoplastic, of which 2(33.33%) were adenocarcinoma and 1(16.67%) were squamous cell carcinoma. Among 61 cases of stomach biopsies 34(55.74%) showed non-neoplastic lesions and 27(44.26%) were neoplastic, of which 1(1.64%) case was adenoma and 25(40.98%) were adenocarcinoma. Among 15 cases of duodenal biopsies 13(86.67%) cases showed non-neoplastic lesions and 2(13.33%) were neoplastic one of which was adenocarcinoma (6.67%). Among 135 cases endoscopist reported 82(60.74%) cases as neoplastic and 53(39.26%) as non-neoplastic, whereas histopathology revealed 77(57.03%) cases neoplastic and 58(42.97%) cases non-neoplastic. Conclusion: Common site of upper GIT endoscopic biopsy is stomach which are mostly neoplastic lesion; however, most common malignancy is squamous cell carcinoma of the oesophagus. Journal of Current and Advance Medical Research 2019;6(1):42-46